Figure of Speech Analysis of The Thrill of it All Album by Sam Smith Using Perrine’s Theory and Its Contribution of Teaching Poetry - Triadi Prasetyo; Fitri Yulianti (International Journal of Research in Education, 2022)
The main aim of this research is to identify the types of Figure of Speeches in Sam Smith’s songs’ lyrics in the album The Thrill of It All, to identify the Figure of Speech most dominant in Sam Smith’s songs’ lyrics in the album The Thrill of It All, and to find out the contributions of Sam Smith’s songs’ lyrics in the album The Thrill of It All in teaching Poetry. This research is a qualitative research which analyzes the Figure of Speech Analysis of The Thrill of It All Album by Sam Smith using Perrine’s Theory and It’s Contribution of Teaching Poetry. Documentary research is used to collect the data, not only collecting and writing in quoting form but also finding the result of the analysis of the document. The data of the research are analyzed by listening, reading, identifying, classifying, calculating, and making a table of the data. The result indicated that the writer found 8 kinds of figures of Speech which are found in The Thrill of It All song’s album by Sam Smith. They are metaphor (7.8%), personification (6.2%), apostrophe (3.8%), synecdoche (3.8%), symbol (50.4%), paradox (7%), hyperbole (16.3%), and irony (4.7%). Then, the most dominant Figure of Speech that is used in songs lyrics is Symbol with a percentage 50.4%. The contributions such as this song lyrics could be the media to enhance the knowledge of Poetry, that could attract the student by reading the content of it and improve knowledge of the students of Poetry.